Eefektivitas Sensus Penduduk Tahun 2024 di Kabupaten Sabu Raijua, Nusa Tenggara Timur - Yohanis Uly Kale; Harry Nenobais; Arief Rahman Hakim (Universitas 17 Agustus 1945, 2026)
This study aims to analyze the effectiveness of the implementation of the 2024 Population Census in Sabu Raijua Regency, East Nusa Tenggara Province, as an important component in providing accurate and reliable population data for development planning. The study employs a qualitative approach with data collection techniques including observation, interviews, documentation, and literature review. The research informants consist of the head of the civil registry office, the head of the social affairs office, sub-district heads, data collection officers, and community leaders who are considered to understand the census implementation process. Data analysis was conducted through stages of data reduction, data presentation, and systematic conclusion drawing. The results show that the implementation of the 2024 Population Census in Sabu Raijua Regency has not been fully effective, particularly in terms of inter-agency integration and adaptation to field conditions. Socialization and communication of policies to the community remain limited, resulting in suboptimal consensus and levels of public participation. In addition, the limited number and capacity of data collection officers, along with inadequate facilities and budget support, have also affected the census implementation. Therefore, more intensive socialization efforts, capacity building for officers, and adequate budget and operational facility support are required to improve the effectiveness of future population census implementation.